2019
DOI: 10.21521/mw.6286
|View full text |Cite
|
Sign up to set email alerts
|

Importance for experiments in human medicine of imaging modalities for macroanatomical and histological study of rabbit suprarenal glands

Abstract: The morphological characteristics of the rabbit adrenal glands are currently investigated using routine imaging modalities. The aim of the study was to collect and interpret major findings and information in the literature on the rabbit as an animal model for investigations in humans. The suprarenal glands of thirty-four mature, clinically healthy New Zealand rabbits were studied using anatomical, routine histology, radiology, computed tomography, ultrasonography, and magnetic resonance imaging methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In our investigation, we used the published data (5,6) for the anatomical peculiarities and topography of the studied organs in the rabbit for better orientation. This study is a continuation of the previous study for the rabbit glands (6) and deepens the knowledge for these glands, because it is focused on the macrometric parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our investigation, we used the published data (5,6) for the anatomical peculiarities and topography of the studied organs in the rabbit for better orientation. This study is a continuation of the previous study for the rabbit glands (6) and deepens the knowledge for these glands, because it is focused on the macrometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The left gland is oval and situated laterally to the abdominal aorta. The right gland is closer to the right kidney, while the left gland is in a distance to the left kidney (5,6). The adrenal glands in the cat are situated cranially to the right and respectively the left kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new surgical technologies and their translation from research to the clinical setting require appropriate experimental models [7]. In modern human medicine, the New Zealand white rabbit is an appropriate animal model for anatomical and histological studies because it is calm and tolerant of disorders better than other species [8]. Besides this, nephrectomy is most commonly performed on healthy rabbits for research purposes because it serves as a model for human renal damage and kidney transplantation [9], so a rabbit kidney was used for this study because several important parameters can be evaluated, where tissue morphology and composition can be studied qualitatively and quantitatively [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rsv has been studied for a several decades in different therapeutic research areas and epidemiological studies have observed the relationship between consumption of Rsv and healthy (16,17). Laboratory animals are used in many experimental studies (18)(19)(20)(21). In numerous experimental studies reported that resveratrol possesses many bioactivities and has beneficial for healthy like antioxidant, anti-inflammatory, improving diseases and also has a hepatoprotective effect (22,23).…”
Section: Introductionmentioning
confidence: 99%